THE EFFECT OF METACOGNITIVE STRATEGY TO IMPROVE READING ABILITY OF THE STUDENTS IN STIE ALWASHLIYAH SIBOLGA - Rosmita Ambarita; Vera Kristiana; Ratna Sari Dewi (PROJECT (Professional Journal of English Education), 2022)
The aim of the research was to improve students' ability in reading text by using metacognitive strategy. The subjects of the study was the first semester of the students of STIE ALWASHLIYAH SIBOLGA 2020.They were 30 students. The researcher provided a textual reading media with metacognitive strategy learning methods to help students know about the reading text so that students more active and understood and then the teaching and learning activities efficiently help the students and also more fun. This type of research is experimental research. The research design used is to use statistical groups. With the value of Ttest 124,103 while Ttable 2.0106, from these values we can conclude 1) Method of Metacognitive Strategy and media in reading text can improve students' ability in reading skills 2) Method of Metacognitive Strategy and media in reading text have an important role in improving the students’ abilityin reading skill. Keywords:        Reading, Metacognitive Strategy,Text